It is known that sin x and cos x are both positive but are not equal. If lo g sin x cot 2 x + lo g cos x tan x = 0 , find the value of cos 4 x + cos 2 x + 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
lo g sin x cot 2 x + lo g cos x tan x lo g ( sin x ) 2 lo g ( cot x ) + lo g ( cos x ) lo g ( tan x ) lo g ( sin x ) 2 ( lo g ( cos x ) − lo g ( sin x ) ) + lo g ( cos x ) lo g ( sin x ) − lo g ( cos x ) 2 lo g ( sin x ) lo g ( cos x ) − 2 + lo g ( cos x ) lo g ( sin x ) − 1 2 ( lo g ( sin x ) lo g ( cos x ) ) 2 − 3 lo g ( sin x ) lo g ( cos x ) + 1 ( 2 lo g ( sin x ) lo g ( cos x ) − 1 ) ( lo g ( sin x ) lo g ( cos x ) − 1 ) ⟹ lo g ( sin x ) lo g ( cos x ) ⟹ cos 2 x = 0 Changing to a common log base = 0 = 0 = 0 Multiplying lo g ( sin x ) lo g ( cos x ) throughout = 0 = 0 = 2 1 Since sin x = cos x = sin x
⟹ cos 4 x + cos 2 x + 1 = sin 2 x + cos 2 x + 1 = 1 + 1 = 2
Sir, could you please explain why we cannot consider sinx = cosx as a solution ? Thanks.
Log in to reply
Okay. It's given in the question. Sorry.
It is given in the problem.
"It is known that sin x and cos x are both positive but are not equal."
Problem Loading...
Note Loading...
Set Loading...
Use lo g a 2 b = lo g b a 2 and ( tan x ) − 1 = cot x .
2 lo g sin x cot x − lo g cos x cot x = 0 ⟹ lo g cot x sin x 2 − lo g cot x cos x 1 = 0
⟹ lo g cot x cos x lo g cot x sin x 2 lo g cot x cos x = lo g cot x cos x lo g cot x sin x lo g cot x sin x ⟹ cos 2 x = sin x = 1 − cos 2 x Squaring and rearranging gives: cos 4 x + cos 2 x + 1 = 2